(untitled) (Educational Dimension, 2025)
The article outlines pedagogical technologies for teaching environmental engineering in online learning systems of higher education using open educational resources (OER) with a student-centred approach. A technology integrating OER, including educational videos, online explanations for practical work, modular testing, and e-textbooks, was experimentally tested. The proposed technology was evaluated using a control and experimental group design at two universities. Statistical analysis using Pearson’s chi-squared test showed a significant improvement in learning outcomes for the experimental group exposed to OER (χ2=45.55, p<0.01). The results demonstrate that a student-centred approach leveraging OER is a promising method to enhance the learning of complex subjects like environmental engineering. This study addresses a gap in empirical research on discipline-specific applications of OER. The findings are discussed in the context of recent literature highlighting the benefits of OER for accessibility, engagement, and learning outcomes in higher education. Recommendations are provided for the effective integration of OER by instructors and institutions.